A Land of Canaan : Seek Me with All Your Heart - Book 1 - Wiseman, Beth 1962- (Nashville, Tenn. : Thomas Nelson, 2010)
Emily Detweiler's family moved to Colorado, but she cannot leave behind the tragedy that struck in Ohio, while David Stolzfus, who is unhappy about leaving Pennsylvania, also struggles with a health condition that may kill him.
Keywords: Amish -- Fiction; Colorado -- Fiction; Fiction